2019
DOI: 10.1115/1.4043510
|View full text |Cite
|
Sign up to set email alerts
|

Model and Control System Development for a Distributed Actuation Magnetic Bearing and Thin-Walled Rotor Subject to Noncircularity

Abstract: This paper considers the problem of controlling the vibration of a lightweight thin-walled rotor with a distributed actuation magnetic bearing (DAMB). A theoretical flexible rotor model is developed that shows how multiharmonic vibration arises due to small noncircularity of the rotor cross section. This model predicts a series of resonance conditions that occur when the rotational frequency matches a subharmonic of a system natural frequency. Rotor noncircularity can be measured offline, and the measurement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A harmonic vibration control (HVC) algorithm is applied in parallel with the PD controller to eliminate multi-harmonic vibration of the rotor when rotating. Previously, it has been shown that multi-harmonic vibration of a thin-walled rotor is prone to arise due to a combination of mass-unbalance and non-circularity of the rotor wall [6]. In the present study, the HVC is used to eliminate rotor vibration so that the required vibration control forces can be evaluated and compared.…”
Section: Practical Implementationmentioning
confidence: 98%
See 2 more Smart Citations
“…A harmonic vibration control (HVC) algorithm is applied in parallel with the PD controller to eliminate multi-harmonic vibration of the rotor when rotating. Previously, it has been shown that multi-harmonic vibration of a thin-walled rotor is prone to arise due to a combination of mass-unbalance and non-circularity of the rotor wall [6]. In the present study, the HVC is used to eliminate rotor vibration so that the required vibration control forces can be evaluated and compared.…”
Section: Practical Implementationmentioning
confidence: 98%
“…Significant vibration of the rotor involving higher harmonics of the rotational frequency occurred for this case. This vibration is caused by noncircularity of the rotor cross-section, as well as nonlinear effects from the bearing (see Reference [6]). The effectiveness of the control implementations can be further compared from Figure 15, where Fourier transform data for the rotor vibration signals and coils currents are presented.…”
Section: Damb Force Control Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitation by massunbalance does not occur for these modes. However, excitation can still arise due to interaction of the rotor structure with external components/forces (Chamroon et al, 2019;Cole and Fakkaew, 2018;Cooley and Parker, 2014;Endo et al, 1984). This paper addresses a main challenge in achieving optimal vibration control, which is that these aspects must be correctly accounted for in the system modeling, control configuration, and controller design.…”
Section: Introductionmentioning
confidence: 99%